A Real-Time Time-Dependent Density Functional Tight-Binding Implementation for Semiclassical Excited State Electron-Nuclear Dynamics and Pump-Probe Spectroscopy Simulations - Bonafé, Franco Paúl (2020)
The increasing need to simulate the dynamics of photoexcited molecular systems and nanosystems in the subpicosecond regime demands new efficient tools able to describe the quantum nature of matter at a low computational cost. By combining the power of the approximate DFTB method with the semiclassical Ehrenfest method for nuclear-electron dynamics, we have achieved a real-time time-dependent DFTB (TD-DFTB) implementation that fits such requirements. In addition to enabling the study of nuclear motion effects in photoinduced charge transfer processes, our code adds novel features to the realm of static and time-resolved computational spectroscopies. In particular, the optical properties of periodic materials such as graphene nanoribbons or the use of corrections such as the "LDA+U"and "pseudo SIC"methods to improve the optical properties in some systems can now be handled at the TD-DFTB level. Moreover, the simulation of fully atomistic time-resolved transient absorption spectra and impulsive vibrational spectra can now be achieved within reasonable computing time, owing to the good performance of the implementation and a parallel simulation protocol. Its application to the study of UV/visible light-induced vibrational coherences in molecules is demonstrated and opens a new door into the mechanisms of nonequilibrium ultrafast phenomena in countless materials with relevant applications.